2022
DOI: 10.1111/tbed.14520
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Phlebotomus perniciosus sandfly vectors is positively associated with Toscana virus and Leishmania infantum infection in human blood donors in Murcia Region, southeast Spain

Abstract: Antibodies against Phlebotomus perniciosus sandfly salivary gland homogenate (SGH) and recombinant protein rSP03B, sandfly-borne Toscana virus (TOSV), Sandfly Fever Sicilian virus (SFSV) and Leishmania, as well as DNA of the latter parasite, were investigated in 670 blood samples from 575 human donors in Murcia Region, southeast Spain, in 2017 and 2018. The estimated SGH and rSP03B seroprevalences were 69% and 88%, respectively, although correlation between test results was relatively low (ρ = 0.39). Simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 99 publications
0
4
0
Order By: Relevance
“…While there are no data on the percentage of infected sand flies in this endemic area, it is tempting to speculate that this might result in high levels of parasite transmission. Indeed, previous studies showed that levels of anti-saliva antibodies are a marker of Leishmania transmission in dogs (66) or humans (67). Quinnell et al .…”
Section: Discussionmentioning
confidence: 99%
“…While there are no data on the percentage of infected sand flies in this endemic area, it is tempting to speculate that this might result in high levels of parasite transmission. Indeed, previous studies showed that levels of anti-saliva antibodies are a marker of Leishmania transmission in dogs (66) or humans (67). Quinnell et al .…”
Section: Discussionmentioning
confidence: 99%
“…While there are no data on the percentage of infected sand flies in this endemic area, it is tempting to speculate that this might result in high levels of parasite transmission. Indeed, previous studies showed that levels of anti-saliva antibodies are a marker of Leishmania transmission in dogs ( 65 ) or humans ( 66 ). Quinnell et al also found that this was not predictive of the outcome of the infection ( 65 ).…”
Section: Discussionmentioning
confidence: 99%
“…These studies not only used different serological techniques (IFAT and Direct Agglutination Test [DAT], respectively), but also analyzed different populations (dog owners and outpatients in a tertiary hospital, respectively). In neighboring Spain, regional seroprevalence studies in blood donors have shown values between 1.3 and 7.9% [ 9 , 12 , 31 34 ]. The range of values of true seroprevalence estimated in the present study was similar to these Spanish studies.…”
Section: Discussionmentioning
confidence: 99%
“…Serological techniques were often used to identify asymptomatic infection, and, in humans, target populations have frequently been blood donors, due to ease of access to samples and a higher confidence of the asymptomatic status, since blood donation is usually only permitted after strict symptom and behavior triage by health professionals and exclusion of anemia. In Spain, seroprevalence studies among the general population and blood donors have shown values between 1 and 8%, depending on the region [ 9 , 12 ]. Factors associated with higher asymptomatic prevalence included older age, male sex, dog tutorship, contact with livestock (either at home or in the environment), living in rural communities, and living in a detached house [ 9 , 13 ].…”
Section: Introductionmentioning
confidence: 99%